Detecção de marcadores de resistência a múltiplas drogas na pele de cães com infecção natural por Leishmania (Leishmania) infantum chagasi (Cunha e Chagas, 1937) Shaw, 2002, submetidos a diferentes protocolos de tratamento - Calado, Andréa Maria Campos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The treatment of dogs with visceral leishmaniasis in Brazil has generated controversial debate among various segments of health professionals. On one side, veterinarians pressured by dog owners want to have the right to decide between treatment and euthanasia of their animals. On the other hand, the Ministry of Health and the Ministry of Agriculture, Livestock, and Supply (MAPA) are opposed to treatment because of the risk of creating strains of the parasite resistant to drugs that are also used for human patients. Scientific arguments that can support this controversy should be explored. One possibility for assessing the development of drug resistance can be achieved through research of the expression of Pglycoprotein (P-gp) and multidrug resistance-associated protein (MRP1). These proteins, which are responsible for the MDR phenotype (multiple drug resistance), act as efflux pumps which expel xenobiotics from cells. Using immunohistochemistry, the reactivity of P-gp (clone C494) and MRP1 (clone ABCC1) in the skin of 11 dogs naturally infected by Leishmania (L.) infantum chagasi was analyzed before and after undergoing two treatment protocols: Allopurinol and inactivated vaccine (n=4) and Allopurinol, inactivated vaccine, and domperidone (n=7). Quantification of Leishmania amastigotes in the skin was also achieved via immunohistochemistry. All of the animals after 3 and 6 months of treatment had clinical improvement and tested negative for amastigote forms of the parasite. Yet, the skin of dogs positive for CVL (canine visceral leishmaniasis) expressed P-gp and MRP1 before and after treatment, illustrating that P-gp and MRP1 were neither good markers for evaluating the therapeutic efficacy of CVL nor for predicting the possible states of drug resistance. However, an understanding of the participation of markers for multiple drug resistance in the skin of dogs under treatment for CVL can be of great importance for the development of an ...

O tratamento de cães com leishmaniose visceral no Brasil tem gerado polêmicas discussões entre os diversos segmentos de profissionais da saúde. De um lado os Médicos Veterinários pressionados pelos proprietários dos cães que querem ter o direito de decidir por um tratamento ou pela eutanásia de seus animais; de outro os Ministérios da Saúde e da Agricultura, Pecuária e Abastecimento (MAPA) que se mostram contrários a qualquer tratamento, motivados pelo risco de se criar cepas do parasita resistentes aos fármacos, os quais também podem ser empregados em pacientes humanos. Argumentos científicos que possam embasar essa polêmica devem ser explorados. Uma das possibilidades de se avaliar o desenvolvimento de resistência a fármacos pode ser conseguida por meio da pesquisa da expressão da glicoproteína-P (gp-P) e proteína de resistência a múltiplas drogas (MRP1), que atuam como bombas de efluxo expulsando xenobióticos de células, responsáveis pelo fenótipo MDR (resistência a múltiplas drogas). Avaliamos, pela técnica de imuno-histoquímica, a reatividade da gp-P e MRP1, clone C494 e ABCC1, respectivamente, na pele de 11 cães naturalmente infectados por Leishmania (L.) infantum chagasi antes e após serem submetidos a dois protocolos de tratamento: Alopurinol e vacina inativada (n=4) e Alopurinol, vacina inativada e domperidona (n=7) e quantificamos formas amastigotas na pele pela mesma técnica. Todos os animais após 3 e 6 meses de tratamento tiveram melhora clínica evidente e tiveram contagem negativa de formas amastigotas do parasita. Pele de cães com LV expressaram gp-P e MRP1, antes e após o tratamento, no entanto, este experimento permitiu concluir que a gp-P e MRP1 não foram bons marcadores para avaliar a eficácia terapêutica da LVC e para prever possíveis estados de resistência a fármacos. Todavia, o entendimento sobre a participação de marcadores de resistência a múltiplas drogas na pele de ...
Keywords: Cão; Leishmaniose visceral; Glicoproteinas; Imuno-histoquímica; Marcadores biologicos; Glycoproteins